ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±ŠAçå¦ç”Ÿ é˜…è¯»è¯¾ä¸çŒœè¯ç–ç•¥ä½¿ç”¨è°ƒæŸ¥ä¸Žåˆ†æž - Karmelia, Leni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â  æ‘˜è¦ æ¯å½“é‡åˆ°æ–°è¯æ—¶å¦ç”Ÿå¸¸æŸ¥é˜…è¯å…¸ï¼Œè¿™æ ·å°±ä¸èƒ½åŸ¹å…»å‡ºå¿«é€Ÿé˜…è¯»èƒ½åŠ›ã€‚è€Œå¯¹äºŽä¸è®¤è¯†çš„ä¿¡æ¯ï¼Œé™¤äº†æŸ¥é˜…è¯å…¸ä½œä¸ºè§£å†³åŠžæ³•ï¼Œæˆ‘ä»¬å¯ä»¥å…ˆçŒœæ–°è¯çš„å¤§æ¦‚æ„æ€ã€‚åœ¨é˜…è¯»ä¸ ä½¿ç”¨çŒœè¯ç–ç•¥å¯ä»¥å¸®åŠ©å¦ç”Ÿç†è§£è¯¾æ–‡ï¼Œä¹Ÿèƒ½æé«˜å¿«é€Ÿé˜…è¯»èƒ½åŠ›ã€‚ä¸ºäº†äº†è§£å¦ç”Ÿåœ¨ æ±‰è¯é˜…è¯»è¯¾æ—¶ä½¿ç”¨çŒœè¯ç–ç•¥çš„æƒ…å†µï¼Œç¬”è€…å¯¹ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ ä¸“ä¸š2015å±ŠAçå¦ç”Ÿè¿›è¡Œäº†è§‚å¯Ÿã€è°ƒæŸ¥å’Œæµ‹è¯•ã€‚ä»Žè€Œç¬”è€…èŽ·å¾—çš„åˆ†æžç»“æžœæ˜¯ï¼šæœ‰43,5% å¦ç”Ÿåœ¨é‡åˆ°ç”Ÿè¯çš„æ—¶å€™ç»å¸¸çŒœè¯çš„æ„æ€ã€‚å¦ç”Ÿåœ¨é˜…è¯»çŒœè¯æµ‹è¯•ä¸é€šè¿‡å¥æ³• çº¿ç´¢çŒœè¯çš„æ£ç¡®çŽ‡ä¸º61%ã€é€šè¿‡ä¸Šä¸‹æ–‡åŒä¹‰çº¿ç´¢æ¥çŒœè¯çš„æ£ç¡®çŽ‡ä¸º52%ã€é€šè¿‡Â Â Â  ä¸Šä¸‹æ–‡çš„åä¹‰çº¿ç´¢çš„æ£ç¡®çŽ‡ä¸º65%ã€é€šè¿‡ä¸Šä¸‹æ–‡çš„åˆ—ä¸¾çº¿ç´¢æ¥çŒœè¯çš„æ£ç¡®çŽ‡ä¸º68%ã€é€šè¿‡åæ—çŒœè¯çš„æ£ç¡®çŽ‡ä¸º40%ã€‚è¿™è¯´æ˜Žï¼Œè™½ç„¶ä¸æ˜¯100%å¦ç”Ÿéƒ½ä½¿ç”¨çŒœè¯ç–ç•¥ï¼Œä½†æ˜¯å¦ç”Ÿå¯¹çŒœè¯ç–ç•¥æŒºç†Ÿæ‚‰çš„ã€‚å› æ¤ï¼Œç¬”è€…å»ºè®®æ±‰è¯è€å¸ˆæ›´é¼“åŠ±å¦ç”ŸåŸ¹å…»çŒœè¯èƒ½åŠ›ï¼Œ æé«˜å¦ç”Ÿçš„çŒœè¯è‡ªè§‰æ€§ï¼Œå¢žå¼ºçŒœè¯è‡ªä¿¡ã€‚ å…³é”®è¯ï¼šæ±‰è¯é˜…è¯»ï¼Œé˜…è¯»æŠ€å·§ï¼ŒçŒœè¯ç–ç•¥ Abstract Students often use dictionary when they found new words, this habit will affect their fast reading ability. Beside checking dictionary, it will be better if students can guess the meaning of the words first. The use of guessing strategy can help students understand the text and improve their fast reading ability. The author observed, surveyed and tested the students of Mandarin Education Study Program 2015 Class A Tanjungpura University in order to understand the situation of students in the use of guessing strategy in the reading class. The result of the analysis is 43,5% of the students often guessing the meaning of the words. The correct rate of interpreting through syntax in Chinese reading class is 61%, through context clues which has identical meaning is 52%, through context clues in the opposite sense is 65%, through context clues which enumerated in clues is 68%, and through the component of a Chinese character is 40%. This result shows that although thereâ€™s not 100% of the students are using guessing strategy, but they are quite familiar with the guessing strategy. Therefore, the author suggested that Chinese teachers also need to encourage students to cultivate guessing ability, improve students' guessing consciousness, enhanced self â€“ confidence of guessing words. Keywords: Chinese Reading, Reading Skills, Guessing Strategy